MANAJEMEN MARKETING SEKOLAH BERBASIS INFORMATION AND COMMUNICATION TECHNOLOGY - Fajri, Nur Sobihatul; wiyani, novan ardy (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The purpose of this research is to describe the process of marketing management of an ICT-based school at SMK Citra Bangsa Mandiri Purwokerto. This research uses a qualitative approach with descriptive methods. Data were collected using interview, observation, and documentation techniques. The data collected was then analyzed using Miles and Huberman's model data analysis techniques, namely data reduction, data presentation, and verification. The results of this study indicate that marketing at SMK Citra Bangsa Mandiri Purwokerto is carried out by utilizing ICT especially for school marketing. ICT-based school marketing is carried out through ICT-based school marketing management planning activities, organizing ICT-based school marketing, mobilizing/implementing ICT-based school marketing, supervision of ICT-based school marketing.